Mitigating Mismatch Compression in Differential Local Field Potentials - Vineet Tiruvadi; Samuel James; Bryan Howell; Mosadoluwa Obatusin; Andrea Crowell; Patricio Riva-Posse; Robert E. Gross; Cameron C. McIntyre; Helen S. Mayberg; Robert Butera (IEEE, 2023)
Deep brain stimulation (DBS) devices capable of measuring differential local field potentials ( $\partial $ LFP) enable neural recordings alongside clinical therapy. Efforts to identify oscillatory correlates of various brain disorders, or disease readouts, are growing but must proceed carefully to ensure readouts are not distorted by brain environment. In this report we identified, characterized, and mitigated a major source of distortion in $\partial $ LFP that we introduce as mismatch compression (MC). Using in vivo, in silico, and in vitro models of MC, we showed that impedance mismatches in the two recording electrodes can yield incomplete rejection of stimulation artifact and subsequent gain compression that distorts oscillatory power. We then developed and validated an opensource mitigation pipeline that mitigates the distortions arising from MC. This work enables more reliable oscillatory readouts for adaptive DBS applications.